Uvod v historično-tipološko sistematiko literarnega razvoja - Kos, Janko (Primerjalna književnost, 2002)
An introduction to a historical-typological sistematics of literary development. The article analyses the problem of literary development on various levels, from the development of individual authors and their work, to the development of national literatures, literary orientations and periods, types and genres. Within this framework a differentiation is made between different types of literary development, and their internal and external causes. The possibility of a developmental periodisation with the application of the geistesgeschichtliche method is tested on European literature, with the conclusion that this aspect needs to be complemented by ahistorical and typological aspects. A European model of literary development cannot be applied in the interpretation of the oriental literatures of Antiquity and the Middle Ages. Applying the typological aspect is, however, feasible.
Keywords: history of literature; literarna zgodovina; literarna tipologija; primerjalna književnost; comparative literature